Model test study on seismic performance of new type column-plate hollow high pier. (2018) - Ziqi, Li; Lusong, Yu; Yanyan, Fan
There are many disadvantages in the design of high pier in high intensity zone for traditional circular end-shaped hollow pier. The design concept of multi-column grid pier can improve the seismic performance of high-strength pier. The column-plate hollow high piers not only retain the good seismic performance of the lattice pier, but also improve the longitudinal and transverse stiffness of the hollow high piers, which lays a foundation for the application of the column plate bridge piers to the design of railway bridges. To understand the seismic performance of such piers systematically, a local model of plate pier is made on the basis of the column plate pier of the Zongmu Gou Bridge in this paper. The destructive mode and hysteresis characteristics of the pier are studied by means of pseudo-static test. It provides reference for the seismic design of the piers. The test results show that the column-plate structure as a whole has strong seismic performance. Under seismic loading, the inter-column plates can be completely sheared and destroyed, and the frame columns remain flexible. The energy consumption of the inter-column plate during the destruction process ensures the normal operation of the frame column.